Advances in nanoparticle-based doxorubicin delivery: precision strategies for targeted treatment of triple-negative breast cancer - Navakanth Raju Ramayanam; Sarad Pawar Naik Bukke; Murali Krishna Moka; Himanshu Dehingia; Aditya Bordoloi; Riya Debbarma; Purushothama Reddy Kudumula; Balakrishna Vuyyala; P. Dharani Prasad; Akugizibwe Catherine (Discover Nano)
Abstract Triple-negative breast cancer (TNBC) is a prevalent and aggressive subtype of breast cancer, accounting for approximately 10–15% of all cases. Its lack of hormone receptors and poor clinical prognosis make targeted therapy particularly challenging, leaving chemotherapy as the mainstay treatment. However, conventional chemotherapy is associated with significant limitations, including cardiotoxicity and inadequate tumor cell specificity. Nanoparticle-based drug delivery systems have emerged as a promising strategy for enhancing the therapeutic efficacy of doxorubicin (DOX) in TNBC. Among these, cell membrane-coated nanoparticles, exosome-sheathed porous silica nanoparticles, and FZD7-targeted nanoparticles have demonstrated substantial potential. These platforms improve drug delivery efficiency while minimizing systemic toxicity and adverse effects. Cell membrane-coated nanoparticles evade immune surveillance, allowing for selective targeting of TNBC cells. Exosome-sheathed nanoparticles facilitate the co-delivery of DOX with other therapeutic agents aimed at inhibiting cancer stem cell-driven epithelial-to-mesenchymal transition. FZD7-targeted nanoparticles enhance DOX accumulation within tumor cells by binding specifically to FZD7 receptors, leading to increased apoptosis and reduced cancer cell metabolic activity. This review aims to examine recent advancements in nanoparticle-based delivery systems for DOX in the treatment of TNBC. It further explores various formulations—including liposomes and polymeric nanoparticles—used for DOX delivery, assesses active and passive targeting strategies, and evaluates the advantages of controlled drug release. The review also identifies current gaps in the literature and proposes future research directions to advance the clinical applicability of these systems. Emerging concepts such as the active transport and retention mechanism and macrophage-mediated delivery systems offer new opportunities to improve tumor localization and retention of DOX-loaded nanoparticles. Collectively, these developments underscore the transformative potential of nanoparticle-based DOX delivery in revolutionizing TNBC therapy.